Advances in non-Archimedean analysis : 13th International Conference p-adic Functional Analysis, August 12-16, 2014, University of Paderborn, Paderborn, Germany - International Conference on P-adic Functional Analysis; Glöckner, Helge; Escassut, Alain; Shamseddine, Khodr (Contemporary mathematics, 2016)
This volume contains the Proceedings of the 13th International Conference on $p$-adic Functional Analysis, held from August 12-16, 2014, at the University of Paderborn, Paderborn, Germany.The articles included in this book feature recent developments in various areas of non-Archimedean analysis, non-Archimedean functional analysis, representation theory, number theory, non-Archimedean dynamical systems and applications.Through a combination of new research articles and survey papers, this book provides the reader with an overview of current developments and techniques in non-Archimedean analysis as well as a broad knowledge of some of the sub-areas of this exciting and fast-developing research area.